DESCRIPTION OF DETAILED COMPONENT-BASED TEXTS - Komilova Dilnoza Muhammad qizi (Bright Mind Publishing, 2025)
This article examines the theoretical and functional nature of artistic detail as a key expressive device in literary discourse. Drawing on linguopoetic and stylistic research, the study demonstrates that artistic detail serves not only as a verbal or non-verbal element depicting objects, gestures, psychological states, and everyday realities, but also as a carrier of implicit meaning that enriches the semantic structure of the text. Through detailed analysis of definitions provided in specialized terminological dictionaries and examples from Abdulla Qahhor’s prose, the article highlights how detail creates imagery, achieves verbal economy, and enhances the author’s communicative intent. The findings show that the integration of linguistic and extralinguistic details facilitates associative perception, enabling the reader to reconstruct a vivid representation of fictional reality. The study concludes that artistic detail functions as a central mechanism of literary expressiveness, contributing to both concretization and artistic generalization within the text.
Keywords: Artistic detail, constant, representational, descriptive detail; clarifying detail, character, implicit, artistic text, hidden meaning.